Thermosensitive nanohydrogel of 5-fluorouracil for head and neck cancer: preparation, characterization and cytotoxicity assay - Dalwadi C (Dove Medical Press, 2018)
Chintan Dalwadi, Gayatri Patel Department of Pharmaceutics and Pharmaceutical Technology, Ramanbhai Patel College of Pharmacy, Charotar University of Science and Technology, Changa, Gujarat, India Abstract: Systemic chemotherapy has been shown to produce side effects. A small fraction of the drug reaches the tumor site; other healthy organs or normal tissues get affected or damaged due to the nonspecific action of these cytotoxic agents. Furthermore, due to their short period of activity, repeat injections are often required, which can lead to the exacerbation of side effects and inconvenience. To overcome these obstacles, in this study, we developed controlled and targeted intratumoral injection. Hydrogel was prepared by physical cross-linking method; however, nanohydrogel was prepared using tip probe-sonicator method. Our results revealed that biodegradable and thermosensitive 5-fluorouracil-loaded methylcellulose nanohydrogel synthesized by physical cross-linking method may be a beneficial approach in targeting the therapeutic agent to the tumor site. Keywords: biodegradable, intra tumor, targeted drug delivery